(untitled) (Baghdad Science Journal, 2025)
A series of new 2-quinolone derivatives linked to benzene sulphonyl moieties were performed by many steps: the first step involved preparation of different coumarins (A1,A2) by condensation of different substituted phenols with ethyl acetoacetate. The compound A1 was treated with nitric acid to afford two isomers of nitrocoumarin derivatives (A3) and (A4). The prepared compounds (A2, A3) were treated with hydrazine hydrate to synthesize different 2-quinolone compounds (A5,A6) while the coumarin treated with different amines gave compounds (A7,A8). Then the synthesized 2-quinolone compounds (A5-A8) treated with benzene sulphonyl chloride to afford new sulfonamide derivatives (A9-A12). The synthesized compounds were characterized by FT-IR, 1H-NMR, 13C-NMR spectra and by measurement some of their physical properties.